(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
An inevitable part of software testing entails the generation of test cases. A good test case should have the quality to cover every aspect of test objective. An effective and efficient test case generation is the most chal lenging and time consuming task in software testing. A good test case characteristics to cover more given set of path coverage with reducing time and cost of software development. Researcher have proposed dif ferent techniques to generate test case automatically. However , those techniques also have some drawbacks. To overcome these drawbacks, we introduce a technique (i.e. GA) to generate small numbers of efficient test cases with expectations to cover more given set of target. In this pa per we introduce that Genetic Algorithm is quite useful search method or technique to generate large volume of test cases very effectively and efficiently with multiple domain.